Landasan Pengembangan Kurikulum Pendidikan di Indonesia - Ade Ahmad Mubarok; Siti Aminah; Sukamto Sukamto; Dadang Suherman; Ujang Cepi Berlian (Jurnal Dirosah Islamiyah, 2021)
The purpose of this study is to have a broad understanding of the foundations for curriculum development; identify several curriculum foundations that become the basis for developing the curriculum by various related parties. The formulation of the curriculum either at the stage of ideas, plans, experiences or as a result of its development must refer to or use a strong and solid foundation, so that the curriculum can function and play a role in accordance with the demands of education in accordance with Law Number 20 of 2003 concerning the National Education System. There are four main foundations that form the basis of curriculum development, namely: philosophical landscape, psychological foundation, socio-cultural foundation, as well as scientific and technological foundations. Philosophical assumptions have implications for the formulation of educational goals, the development of educational content or materials, determining strategies, as well as on the role of students and the role of educators. The psychological foundation refers to cognitive, behavioristic, and humanistic learning theories. The socio-cultural foundation has implications for the educational program that will be developed. Meanwhile the scientific and technological foundations are the starting points in developing the curriculum so that it is adaptive to the changes and challenges of the times.